Internalisasi Nilai-Nilai Multikultural Melalui Melalui Pembelajaran IPS Dalam Menumbuhkan Sikap Multikultural Pada Siswa - Melinda, Kartikasari; Indawati, Ninik; Nu Graha, Andi (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
Internalization is a process of individual learning and being accepted as part of society from an early age to adulthood. Multicultural values consist of values of openness, tolerance, and mutual help. Internalization of multicultural values is needed because there are still differences in language among students due to the regional origins of the majority of students. The purpose of this study was to find out multicultural values through social studies learning given by students, explain how to foster multicultural values through social studies learning, and explain the process of internalizing multicultural values through social studies learning. The method used for research is storytelling, learning outside the classroom, and school events held on holidays. By using this method, students' behavior can change from rejecting others who are different to accepting and being friendly with others. These constraints also arise when they imply multicultural values, such as a lack of knowledge in media storytelling techniques used by teachers, lack of learning media in schools, and the conditions in which students.